Relating localized protein motions to the reaction coordinate in coenzyme B12‐dependent enzymes. (21st March 2013) - Jones, Alex R.; Levy, Colin; Hay, Sam; Scrutton, Nigel S.
<x xml:space="preserve">Abstract</x> The classical picture of enzyme catalysis relies on controlling the entropic and enthalpic contributions by manipulating reaction barriers and co‐locating reactants and cofactors to facilitate the reaction chemistry. Catalysis is linked inextricably to the geometry of the enzyme–substrate complex and the chemical/physical properties of the active site, and probably to dynamical contributions that guide reactants along the desired reaction coordinate. Coenzyme B12‐dependent enzymes have remarkable catalytic power and unique properties that enable detailed analysis of the reaction chemistry and associated dynamics. Here we discuss recent developments that are beginning to provide atomistic insight into how coenzyme B12‐dependent enzymes steer reactants along the reaction coordinate. Such insight will ultimately generate 'movies' of the catalytic process across all relevant time scales. In the longer term, this will enable more predictive engineering of this class of enzyme to achieve new and desirable chemical outcomes.